Studi Korelasi Penggunaan Makeup Sehari-Hari Dengan Kepercayaan Diri Pada Mahasiswi Fakultas Mipa Universitas Negeri Jakarta - Putri Nabila; Dra. Eti Herawati; Lilis Jubaedah (Mathematics Education Study Program, 2025)
To support individual confidence can be seen through physical appearance, one of the factors that can support the confidence of women or female students is the use of makeup. This study aims to find out the extent of the correlation between daily makeup use and self-confidence in students of the Faculty of Mathematics and Natural Sciences, State University of Jakarta. This study uses a quantitative method of correlation by conducting a survey, namely making a questionnaire consisting of 35 statements. The sample of this study was 82 students of the Faculty of Mathematics and Natural Sciences, State University of Jakarta class of 2021 and was selected using a simple random sampling technique. The indicators on the variables of makeup use are duration and frequency, while the confidence variables are self-confidence and ability, responsibility, rationality and rationality. The correlation results obtained in this study of 0.299 which are in the range of 0.200-0.399 show that the correlation level is low and positive.